Pengembangan Lembar Kerja Peserta Didik (Lkpd) Berbasis Etnomatematika: Pengembangan - Fitriana, Eva; Dwi Putra, Erik; Murtinasari, Frida (Universitas Islam Jember, 2024)
The research aims to develop ethnomathematics-based LKPD. Based on the needs of students they can increase their interest in learning, influencing ability, understanding, and curiosity. This research is the research and development of the 4D model, namely define, design, develop, and disseminate (distribution) consisting of validity, practicality, and effectiveness. The instruments used were (1) approval/validation sheets, (2) perceptions of the implementation of LKPD in learning, (3) student response questionnaires, and (4) learning completion tests. The LKPD received a score from media validation of 4.2 and a score from material validation of 4.4 so it met the valid criteria. In the practicality category, the LKPD is declared practical because it meets the value with an average score of 4.3 in the very practical category. The effectiveness of the LKPD was obtained from the student response questionnaire assessment with an average score of 4.8 in the good category. So that the LKPD is declared effective, the ethnomathematics-based LKPD is declared feasible and can be used in learning. Keywords: student worksheets, ethnomathematics